Production of cuttings and nutrient export by Coffea canéfora in different periods in the Southwestern Amazon - Patrícia A. Bazoni; Marcelo C. Espindula; Larissa F. B. de Araújo; Jaqueline M. Vasconcelos; Marcela Campanharo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Cutting is the main vegetative propagation method used for the production of Coffea canephora plantlets. In this method, parent plants are conducted in a specific field, called clonal garden, which must be managed to produce clonal cuttings. The objective of this study was to evaluate the production of cuttings and the export of nutrients by Coffea canephora in different periods in the Southwestern Amazon. The experiment was carried out in a 6 × 3 split-plot scheme (repeated measures in time), consisting of the combination of six clonal Coffea canephora genotypes (plot) and three cutting collection periods (subplots). The genotypes were: C-057, C-088, C-089, C-125, C-130 and C-160; and the evaluation sampling times were January/2017, May/2017 and September/2017. The applied design was a completely randomized design with four repetitions. The dry season, from May to September, promotes lower orthotropic stem dry mass accumulation by Coffea canephora, but allows obtaining a larger number of viable cuttings for the production of clonal plantlets. Nutrient accumulation by orthotropic stems for cutting production follows the following order: N > K > Ca > Mg > S > P > Mn > Fe > Zn > Cu. Nutrient export by the cuttings follows a descending order: K > N > Ca > Mg > P > S > Mn > Fe > Zn > Cu.